Editor's Highlight: PCB126 Exposure Increases Risk for Peripheral Vascular Diseases in a Liver Injury Mouse Model. (31st August 2017) - Wahlang, Banrida; Barney, Jazmyne; Thompson, Brendan; Wang, Chunyan; Hamad, Omer M; Hoffman, Jessie B; Petriello, Michael C; Morris, Andrew J; Hennig, Bernhard
Abstract: The liver is vital for xenobiotic and endobiotic metabolism. Previously, we demonstrated that a compromised liver worsened toxicity associated with exposure to polychlorinated biphenyls (PCBs), through disruption of energy homeostasis. However, the role of a compromised liver in defining dioxin-like PCB126 toxicity on the peripheral vasculature and associated inflammatory diseases is yet to be studied. This study investigated the effects of PCB126 on vascular inflammation linked to hepatic dysfunction utilizing a liver injury mouse model. Male C57Bl/6 mice were fed either an amino acid control diet (CD) or a methionine-choline deficient (MCD) diet in this 14-week study. Mice were exposed to PCB126 (0.5 mg/kg) and analyzed for inflammatory, calorimetric and metabolic parameters. MCD diet-fed mice demonstrated steatosis, indicative of a compromised liver. Mice fed the MCD-diet and subsequently exposed to PCB126 manifested lower body fat mass, increased liver to body weight ratio and alterations in hepatic gene expression related to lipid and carbohydrate metabolism, implicating metabolic disturbances. PCB126-induced steatosis irrespective of the diet type, but only the MCD + PCB126 group exhibited steatohepatitis and fibrosis. Furthermore, PCB126 exposure in MCD-fed mice led to increased plasma inflammatory markers such as Icam-1, plasminogen activator inhibitor-1 and proatherogenic trimethylamine-N-oxide, suggesting inflammation of the peripheral vasculature that is characteristic of atherosclerosis. Taken together, our data provide new evidence of a link between a compromised liver, PCB-mediated hepatic inflammation and vascular inflammatory markers, suggesting that environmental pollutants can promote crosstalk between different organ systems, leading to inflammatory disease pathologies.